TECHNOLOGY OPTIONS FOR MODERN DIAGNOSTIC METHOD-PCR (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
At present, variants of PCR staging have been developed aimed at solving the following problems: increasing the efficiency of the reaction and reducing the risk of non-specific products formation; qualitative and quantitative analysis of the desired regions of the DNA/RNA molecule.